Kegiatan outbond sebagai media pendidikan karakter Pancasila pada pendidikan anak usia dini - Purwastuti, Lusila Andriani (Jurnal Pendidikan Karakter, 2022)
This study aims to examine character education learning media that are in accordance with the principles of learning in early childhood. Outbound can be used as a character learning medium in Early Childhood Education. Outbound as a character learning medium is an essentially learning approach that uses the principle of playing while learning, experience learning, which is adapted to aspects of child development. This research is a research and development following the model of Thiagarajan which consists of define, design, development, and disseminate. The results of this study indicate that outbound in early childhood education is adapted from outbound games commonly used in recreational places which are embedded in learning themes and sub-themes. Learning activities are adapted to learning in kindergarten which consists of an introduction, core, and closing. Outbound activities for PAUD consist of games Reaching for the Stars, Chain of Love, Defending the Fort, Building a Lighthouse, and Maze of Social Justice. The five forms of this game are learning that contains the values of divinity, humanity, nationalism, democracy, and welfare. Apart from that, outbound learning also includes the values of cooperation, empathy, tolerance, leadership, and being able to stand the test of facing challenges. Outbound is an effective learning media for national character education for early childhood.